Assembling MXene with bio-phytic acid: Improving the fire safety and comprehensive properties of epoxy resin. (June 2022) - Meng, Weihua; Song, Yuying; Zhai, Ke; Di, Hang; Ma, Haiyun; Bi, Xue; Xu, Jianzhong; Fang, Lide
Abstract: Phytic acid (PA)-modified MXene (P-MXene) was prepared combination selective etching with assemble method, and was mixed with epoxy resin (EP) to investigated its flame retardancy, thermal conductivity, conductivity and mechanical properties. P-MXene exhibited two-dimensional single layer structure and had good char-forming property with 86.7% char residue at 800 °C. The cone calorimetry test results showed that P-MXene endowed EP with excellent flame retardancy. Compared with pure EP, the peak heat release rate, peak smoke release rate, peak CO generation rate, and peak CO2 generation rate of EP composites with 2 phr P-MXene decreased by 38.6%, 31.6%, 38.7% and 40.6%, respectively. The flame retardant mechanism was attributed to physical barrier, catalyzing carbonization effect, oxidative thermal degradation and physical barrier effect. Additionally, the conductivity and mechanical properties of EP composites were slightly reduced. This work provides a promising method to design multifunctional polymers. Highlights: P-MXene was synthesized by liquid etching and in situ assemble to improve the flame retardancy of EP. P-MXene endowed EP with excellent flame retardancy with decreased PHRR, PSPR, PCOP and PCO2P value. The flame-retardant mechanism is the combination of gas phase and condensed phase. EP/P-MXene composites had remarkable comprehensive performance, including mechanical property and thermal conductivity.